Mirror-Reading Moral Issues in Paul’s Letters - Gupta, Nijay K. (Journal for the study of the New Testament, 2012)
Biblical interpreters have long recognized the need to engage in mirror-reading when it comes to studying the apostle Paul’s letters, as they are ‘occasional’ writings, where an understanding of the context of the wider conversation gives insight into the proper understanding of the text’s meaning. In 1987, John Barclay made a key contribution to the practice of interpreting Paul’s letters by offering a criticism of unwieldy attempts at mirror-reading and by presenting a methodological standard for how mirror-reading can and should be carried out. While Barclay’s article has brought a helpful critical standard to the practice of mirror-reading Paul’s letters in general, his methodology was focused specifically on texts where the interest is in false teaching and polemics (as in his test-case of Galatians). This article attempts to draw from the approach that Barclay set forth with an interest in tailoring it to fit the needs of studying an occasional letter where moral issues are central to the text. After examining Barclay’s method, addressing the need for a similar approach to moral concerns in Paul’s letters, and developing a new method appropriate to that subject matter, the topic of sexual immorality in 1 Thessalonians and Romans will serve as test-cases of this re-applied approach to mirror-reading.